EFFECTS OF DIFFERENT CONCENTRATIONS OF FRESH AND DRIED CALOTROPIS PROCERA (SODOM APPLE) EXTRACT ON COW MILK COAGULATING TIME, CHEESE YIELD AND ORGANOLEPTIC PROPERTIES OF WEST AFRICAN SOFT CHEESE (WAGASHIE) - S. K., Chikpah; G. A., Teye; M., Teye; F. F., Mawuli (European Scientific Journal, ESJ, 2014)
This study was conducted to determine the effects of different concentrations of fresh and dried Calotropis procera extract (CPE) on cow milk coagulating time, yield, whey volume and organoleptic properties of West Africa soft cheese (WASC) (wagashie). Three different concentrations of fresh and dried CPE (F2, F5, and F7) and (D2, D5, and D7) were respectively obtained from 2 g, 5 g and 7 g (on dry matter basis) of fresh and dried Calotropis procera. Each of the extracts prepared was used as a sole coagulant of pasteurized cow milk and the effects on the milk coagulating time, WASC yield, whey volume, and organoleptic properties of WASC were determined. All the parameters assessed were significantly (p < 0.05) influenced by the type and concentration of CPE. The average milk coagulating time, cheese yield and whey volume ranged between 14 - 29 minutes, 134.9 – 237.4 (g/l) and 657.1 – 771.4 (ml/l) respectively. The coagulating time of the fresh Calotropis procera extract (FCPE) treatments were significantly shorter than that of the dried Calotropis procera extract (DCPE) treatments. Generally, milk coagulating time decreased with increased concentration of CPE. The yield of WASC was significantly (p < 0.05) higher among DCPE treatments as compared to FCPE treatments. Cheese yield increased with increased concentration of CPE. There was strong negative correlation (p < 0.05) between milk coagulating time and WASC yield for both FCPE and DCPE treatments. The type and concentration of CPE added to the milk had significant (P < 0.05) effects on the organoleptic properties (taste, colour, texture and overall acceptability) of the WASC produced. Generally, extracts from 2 g of Calotropis had better performance in terms of cheese yield, and organoleptic properties of WASC (wagashie).